1993
DOI: 10.1007/bf00717052
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of articular cartilage proteoglycan and link protein in situ using monoclonal antibodies and lectin-binding methods

Abstract: Lectins have specificity for certain carbohydrate structures in macromolecules. Lectins are, therefore, useful histochemical tools for demonstrating the composition and localization of components of connective tissue matrices, such as articular cartilage. In order to assess the significance of observed lectin-binding patterns, experiments were performed in which monoclonal antibodies against chondroitin sulphate- and keratan sulphate-containing proteoglycans and link proteins were applied to sections of bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…It may inhibit neural crest cell migration (Perris et al, 1991) and can inhibit cell adhesion and neurite outgrowth in vitro (Cole and McCabe, 1991;Smith-Thomas et al, 1994). It thus shows similar properties to CS and furthermore could be a binding site for PNA (Hoedt-Schmidt et al, 1993).…”
Section: Introductionmentioning
confidence: 68%
“…It may inhibit neural crest cell migration (Perris et al, 1991) and can inhibit cell adhesion and neurite outgrowth in vitro (Cole and McCabe, 1991;Smith-Thomas et al, 1994). It thus shows similar properties to CS and furthermore could be a binding site for PNA (Hoedt-Schmidt et al, 1993).…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, a cell surface proteoglycan that bears both chondroitin and heparan sulfate chains (19) is transiently lost when epithelia change their shape and is transiently expressed by mesenchymal cells undergoing morphogenetic tissue interactions (24,25). In this context, since specific breakdown of chondroitin sulfate chain is required for binding of SBA (6), the overexpression of SBA binding sites on the cell membrane of the hyperplastic dental epithelium may be interpreted as resulting from an alteration or degradation of carbohydrate moieties of proteoglycans (and possibly those of glycolipids and glycoproteins) on such cell surface. This is probably due secondary to pathological aberrations residing in the dento-skeletal microenvironment of OP/OP mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous finding demonstrated that UTI may be able to bind hyaluronic acid via the LP molecule since UTI fails to directly bind hyaluronic acid (7). Link protein is present on a wide variety of cells, including skin and fibroblasts (8), chondrocytes (9), chondrosarcoma cells (10 -13), synovial cells (14), aorta (15), trachea (16), and hepatocytes (17)(18)(19). Characteristics of the LP molecule have been studied by a number of different laboratories (20,21), and it has been shown to mediate the interaction between proteoglycans and hyaluronic acid (22,23), a characteristic that may allow it to demonstrate pericellular matrix formation and stabilization (hyaluronic acid-rich matrix formation) (17).…”
Section: Urinary Trypsin Inhibitor (Uti)mentioning
confidence: 99%